1978
DOI: 10.1111/j.1095-8649.1978.tb03473.x
|View full text |Cite
|
Sign up to set email alerts
|

The production of brown trout, Salmo trutta in tributaries of the Upper Wye, Wales

Abstract: The population density, age structure, biomass, growth and production of brown trout were investigated in four tributaries of the upper River Wye. The populations at each site were largely maintained by immigration from nursery areas. Abundance of separate year classes at sites on the three largest tributaries reached a peak at age 2 + . On the smallest stream numbers reached a peak at 1 + . Recruitment occurred throughout the year but decreased with age of year classes. Maximum O+ densities ranged from 0.04 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

1982
1982
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 13 publications
2
18
0
1
Order By: Relevance
“…Similar instability was reported for brown trout in tributary streams of the upper River Wye, Wales (Milner et al 1978(Milner et al , 1979. Unstable trout stocks may largely be maintained by immigration.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Similar instability was reported for brown trout in tributary streams of the upper River Wye, Wales (Milner et al 1978(Milner et al , 1979. Unstable trout stocks may largely be maintained by immigration.…”
Section: Discussionmentioning
confidence: 53%
“…The extent of immigration may vary considerably between stocks and streams. Allen (1951) found almost no migration of brown trout between specific sampling sites in the Horokiwi Stream, whereas in this study and in other streams considerable immigrations have been observed (Horton 196 1, Mills 1969, Milner et al 1978. However, immigration evidently is an important recruitment process in downstream reaches of streams and migration may provide a mechanism to optimise utilization of the total stream habitat, with trout taking up positions appropriate to their size and territorial requirement.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…From 1977 to 1980, migrating spawners were tagged with Carlin or Floy-tags to determine their most upstream position in the tributary during the spawning period. In -1978In and 1980In -1981 were counted and mapped (no. km-') throughout the spawning period in zones A and B.…”
Section: Methodsmentioning
confidence: 99%
“…De plus, les valeurs de G, obtenues sur le ruisseau de Kernec pour ces deux classes d'âge, sont semblables à celles observées par EGGLISHAW et SHACKLEY (1977) sur un ruisseau écossais. Par ailleurs, la valeur souvent élevée des tempé-ratures de l'eau hivernales en Bretagne ne provoque généralement pas d'arrêt de croissance durant l'hiver, à la différence des constations faites dans des régions plus nordiques (EGGLISHAW et SHACKLEY, ibidem;MILNER et al, 1978;ELLIOTT, 1985ELLIOTT, et 1988KELLY-QUINN et BRACKEN, 1988). Cette observation se traduit souvent sur les écailles de la truite de cette région par une délimitation, entre la première et la deuxième année de croissance, visible uniquement par l'augmentation de l'espacement intercirculi (BAGLINIÈREet LE LOUARN, 1987).…”
Section: Analyse De La Croissanceunclassified